Tissue Disposition and Withdrawal Time of Fosfomycin in Swines after Oral and Intramuscular Administration - Pérez, Denisa Soledad (2013)
A HPLC-MS/MS method, which was suitable to be used in withdrawal time studies, was validated for the determination of fosfomycin in swine muscle, liver, kidney and skin-fat. Therefore, the withdrawal time of fosfomycin in swines, considering a MRL of 0.5 μg/mL was studied. Forty-eight pigs were assigned to two groups; in group one, fosfomycin was orally administered daily with 30 mg⁄kg bw and to the other group a dose of 15 mg⁄kg bw of the antibiotic was intramuscularly administered. Pigs were slaughtered 24, 48, 72 and 96 hours later of oral treatment withdrawn and post intramuscular treatment. The longer WDT was 2.95 days for the PO administration and 1.73 days for the IM administration; therefore, WDTs of 3 days and 2 days, respectively, could be assigned as a precautionary principle for public health, without a significant economic impact for the swine producer.